Bedside Itinerant Teachers' Experience in Interdisciplinary Collaboration and Their Professional Identity - Wen-Chang Teng; Rui-Long Yan (National Taipei University of Education, 2020)
In order to protect the right to education for children with severe diseases, special education teachers have stepped into the hospitals to become hospital bedside itinerant teachers and have served as the bridge between education and healthcare professions. The job of bedside teachers differs from that of school teachers in that it spanned two different professional fields, which in turn affects the perception of professional identity. This study attempts to understand the interdisciplinary collaborative experience of bedside teachers and their professional identity. This study adopts the qualitative research approach. After acquiring consent from the institution, nine bedside itinerant teachers were recruited. One to two-hour in-depth semi-structured interviews were conducted one to three times for each subject. Inductive content qualitative analysis was used to further understand the bedside teaching experience. The challenges in interdisciplinary collaboration were found: (1) interdisciplinary collaboration requires mutual exploration; (2) teaching in the hospital requires reshaping of pedagogical structure; (3) struggling with facing life and death issues; (4) crossing fields challenges the perception of professional identity. With these challenges, the bedside teachers' experiences of identity were: (1) using self as research material to decipher chaos; (2) regrouping and re-fusion of identity. Based on the results, issues surrounding interdisciplinary collaboration and professional identity were discussed and recommendations were proposed.